Order of the major constituents in sign languages: implications for all language - Napoli, Donna Jo; Sutton-Spence, Rachel (Frontiers in Psychology, 2014)
A survey of reports of sign order from forty-two sign languages leads to a handful of generalizations. Two accounts emerge, one amodal and the other modal. We argue that universal pressures are at work with respect to some generalizations, but that pressure from the visual modality is at work with respect to others. Together, these pressures conspire to make all sign languages order their major constituents SOV or SVO. This study leads us to the conclusion that the order of S with regard to VP is not determined by the grammar of a language (spoken or sign), but rather by sensorimotor system concerns.